Evaluation of the efficacy of icariin against heat stress-induced spermatogenic dysfunction in the testes of dogs - Li, Baoan; Xie, Liuwei; Song, Mingqiang; Zhang, Xiumin; Yan, Chuanguo; Gao, Wanpeng; Wang, Wenxing; Yang, Yang (Frontiers in Veterinary Science, 2025)
IntroductionThis study examines the detrimental effects of high-temperature environments on canine testicular function and reproductive health, and investigates the potential of Epimedii Folium, particularly its active component icariin, in alleviating these effects and improving testicular function.MethodsA completely randomized single-factor design was employed, involving 24 adult male Beagle dogs (9.82 ± 0.73 kg) assigned randomly to four treatment groups, with six dogs in each group. The groups included a negative control group (“Control”), a positive control group exposed to testicular heat stress (“Model”), and two icariin-treated groups receiving daily doses of 0.5 g/kg (Icariin-L) and 1.0 g/kg (Icariin-H), respectively. All groups, except the negative control, underwent a testicular heat stress model to induce damage and assess the effects of icariin on sperm quality, testicular function, hormone levels, protein expression, and testicular histological changes.ResultsIcariin supplementation improved sperm quality under heat stress, as indicated by increased total sperm count and motility, along with a reduction in sperm malformation rate (p < 0.01). It also restored adenosine triphosphate (ATPase) activities (Na+-K+-ATPase, Mg2+-ATPase, and Ca2+-ATPase) and serum hormone levels (GnRH, LH, and E2) (p < 0.01). Western blot analysis revealed that icariin upregulated steroidogenic proteins (STAR, 17βHSD, and CYP450) and the tight junction protein ZO-1 (p < 0.01), while downregulating the BAX expression (a key regulator of mitochondrial apoptosis) and enhancing the BCL-2 expression (a major anti-apoptotic factor in the BCL-2 family) (p < 0.01). Histological assessments demonstrated that icariin mitigated heat-induced damage to seminiferous tubules, epithelial thinning, and spermatogonia degeneration. Furthermore, molecular docking analysis confirmed a strong binding affinity between icariin and 17βHSD, mediated by hydrogen bonding and hydrophobic interactions.ConclusionThese findings suggest that icariin may alleviate testicular heat stress by modulating testosterone synthesis, enhancing ATPase function, restoring blood–testis barrier integrity, and inhibiting apoptosis. The dose-dependent efficacy (1.0 g/kg > 0.5 g/kg) supports the potential of icariin as a possible therapeutic agent for improving reproductive health in dogs exposed to high-temperature environments.